Exogenous Pancreatic Kallikrein Improves Diabetic Cardiomyopathy in Streptozotocin-Induced Diabetes - Wu, Meng; Yang, Yeping; Wang, Meng; Zeng, Fangfang; Li, Qin; Liu, Wenjuan; Guo, Shizhe; He, Min; Wang, Yi; Huang, Jie; Zhou, Linuo; Li, Yiming; et al. (Frontiers in Pharmacology, 2018)
Aims: To evaluate the protective effects of exogenous pancreatic kallikrein (PKK) treatment on diabetic cardiomyopathy (DCM) and explore the underlying mechanisms. Methods and results: Streptozotocin (STZ)-induced diabetic rats, a type 1 diabetic model, were treated with either PKK or saline for 12 weeks. Non-diabetic rats were used as controls. PKK administration attenuated the mitochondria swelling, Z line misalignments, myofibrosis and interstitial collagen accumulation in diabetic myocardial tissue. The oxidative stress imbalance including increased nitrotyrosine, decreased anti-oxidative components such as nuclear receptor nuclear factor like 2 (Nrf2), glutathione peroxidase 1(GPx-1), catalase (CAT) and superoxide dismutase (SOD), were recovered in the heart of PKK-treated diabetic rats. In diabetic rats, protein expression of TGF-β1 and accumulation of collagen I in the heart tissues was decreased after PKK administration. Markers for inflammation were decreased in diabetic rats by PKK treatment. Compared to diabetic rats, PKK reversed the degradation of IκB-α, an inhibitive element of heterotrimer nuclear factor kappa B (NF-κB). The endothelial nitric oxide synthase (eNOS) protein and myocardial nitrate/nitrite were impaired in the heart of diabetic rats, which, however, were restored after PKK treatment. The sarcoplasmic reticulum Ca2+-ATPase 2 (SERCA2) and phospholamban (PLN) were mishandled in diabetic rats, while were rectified in PKK-treated diabetic rats. The plasma NT-proBNP level was increased in diabetic rats while was reduced with PKK treatment. Conclusions: PKK protects against diabetic cardiomyopathy via reducing fibrosis, inflammation, and oxidative stress, promoting nitric oxide production, as well as restoring the function of the calcium channel.